The Effect of The Concept of Cultural Code on The Development of Intercultural Communication (Eurasian Research Bulletin, 2024)
This article discusses the place and role of the concept of cultural code in the development of intercultural communication. It also provides detailed information about the circumstances of the formation of the cultural code and the processes of change. Analytical approaches about the differences in the development of societies and cultural codes have been implemented using international experiences.